The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/microorganisms11102576
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hepatitis E Virus in Wild Boar and Red Deer in Portugal

Humberto Pires,
Luís Cardoso,
Ana Patrícia Lopes
et al.

Abstract: Hepatitis E virus (HEV) is a zoonotic foodborne virus with an annual infection prevalence of 20 million human cases, which seriously affects public health and economic development in both developed and developing countries. To better understand the epidemiology of HEV in Central Portugal, a cross-sectional study was conducted from 2016 to 2023 with sera samples from wild ungulates. The seroprevalence and risk factors for HEV seropositivity were evaluated in the present study. Specifically, antibodies against H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…by species ranged from 5.4% in red deer to 35.5% in wild boar, the most often hunted game animals in Portugal. Nevertheless, data on the presence of zoonotic diseases in wild ungulates used for human consumption are generally sparse in Portugal [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by species ranged from 5.4% in red deer to 35.5% in wild boar, the most often hunted game animals in Portugal. Nevertheless, data on the presence of zoonotic diseases in wild ungulates used for human consumption are generally sparse in Portugal [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wild boars are also known to be carriers of numerous other infectious diseases and zoonoses [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This expansion has led to various implications, especially concerning infectious diseases and zoonotic risks associated with wild boar. Studies have identified wild boar as potential reservoirs for infectious agents like HEV, Coxiella and Brucella [19][20][21]. The presence of these pathogens in wild boar poses risks not only to wildlife but also to domestic animals and humans due to potential zoonotic transmission.…”
Section: Introductionmentioning
confidence: 99%